2022
DOI: 10.1136/bmjopen-2022-061525
|View full text |Cite
|
Sign up to set email alerts
|

Association between purpose in life and healthcare use among women and men in Germany: cross-sectional analysis of the nationally representative German Socio-Economic Panel (GSOEP) study

Abstract: ObjectivesIt remains almost unknown whether purpose in life is associated with healthcare use (HCU) in general. Therefore, the goal of this study was to examine the association between purpose in life and HCU (in terms of frequency of outpatient physician visits and hospitalisation) stratified by sex.DesignCross-sectional study.Setting and participantsA representative sample of the general adult population in Germany (n=1238; collected from September 2020 to February 2021); taken from the innovation sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…In some other studies, a negative relationship was observed between smoking and the use of health services (Homaie Rad et al, 2015). Smoking was not linked to HSU in one research (Hajek and König, 2022).…”
Section: Smokingmentioning
confidence: 75%
See 4 more Smart Citations
“…In some other studies, a negative relationship was observed between smoking and the use of health services (Homaie Rad et al, 2015). Smoking was not linked to HSU in one research (Hajek and König, 2022).…”
Section: Smokingmentioning
confidence: 75%
“…, 2011; Esmailnasab et al. , 2014; André Hajek and König, 2022; Hansen et al , 2012; Hassanzadeh et al. , 2013; Tountas et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations